Complications of Temporomandibular Joint Surgery - Bouloux, Gary F. (Springer International Publishing : Imprint: Springer, 2017)
This book provides detailed guidance on the recognition and treatment of the complications most frequently encountered in patients who undergo temporomandibular joint surgery. Evidence-based guidelines are referred to whenever possible, and when such guidelines are lacking, the preferred current approaches to diagnosis and management are described. In addition, the pathophysiology of each complication is discussed and advice offered on how to ensure that the correct surgical procedure is chosen for the individual patient, thereby minimizing the risk of complications. Illustrative cases are included to further highlight key points. The authors are experienced surgeons and pioneers in the field of temporomandibular joint surgery. Complications of Temporomandibular Joint Surgery will be of value for all who work in this technically very challenging field and regularly have to deal with the issues posed by a difficult patient population and the risk of suboptimal outcomes.
Keywords: Dentistry.; Medicine.; Oral surgery.; Maxillofacial surgery.; elektronické knihy; electronic books